Erectile Dysfunction in Brazilian Primary Health Care: Dealing with Medicalization - Antônio Augusto Dall’Agnol Modesto MD, PhD; Marcia Thereza Couto PhD (American Journal of Men's Health, 2018)
Erectile dysfunction (ED) is a common sexual problem and has been attracting growing interest from the field of medicine. The pharmaceutical industry works together with medical associations to popularize the theme, emphasizing individual enhancement and medication, besides reinforcing an idea of a male sexuality defined by the ability to have an erection and penetrate. Patients worried about erection problems search for general practitioners (GPs), frequently without a clear complaint, and a comprehensive primary health care (PHC) must be capable of dealing with these issues considering medicalization and disease mongering. This article discusses how PHC physicians take (and might take) care of men with erection problems, and how users perceive it and search for help in two cities in the State of São Paulo, Brazil. The qualitative research, performed in five PHC services, included semistructured interviews with 16 GPs and 15 adult male users. The adult male users were invited by their doctors during consultations where questions about prostate, ED, or other sexual problems arose. Interviews were transcribed and submitted for content analysis. In addition, the five participating services were observed with help of a specific script. Results indicate that ED is frequently a hidden agenda and that doctors have trouble approaching the problem, usually focusing on the biological aspects. Based on empirical data and literature, this work indicates some measures to qualify the care of men with ED in PHC which includes contemplating users’ questions, respecting their autonomy, avoiding an antidrug stance, and considering drug and nondrug approaches as a continuum of resources.